Simbol Nasionalisme Dalam Music Video â€œRewind Indonesia 2021â€ - Putranto, Teguh Dwi (Soetomo Communication and Humanities, 2022)
At the end of 2021, Rewind Indonesia 2021 returns with a collection of topics that have been discussed throughout the year. The video is uploaded by the Indonesian Youtubers account and has a total duration of approximately 21 minutes. Various famous people appear in the video, including actors, athletes and digital content creators. Rewind Indonesia 2021 contains a message that serves as a reminder for every young person who watches the film that the future of Indonesia and the country is in the hands of young people who want better things. This study aims to find out how the symbol of nationalism in the music video "Rewind Indonesia 2021". The method used in this study is the semiotics of Charles Sanders Peirce in the music video "Rewind Indonesia 2021" on the Youtube Channel Indonesian Youtubers. The conclusion of this study is that the symbol of nationalism in the music video "Rewind Indonesia 2021" is a symbol related to identity as the Indonesian nation, a symbol of protection (please help), a symbol that gives encouragement, and a symbol of resurrection.